Impelementasi Pendekatan Humanistik Guru dalam Meningkatkan Efikasi Diri Siswa Sekolah Dasar - Shadrina Afra; Rusdiono Muryanto; Effy Mulyasari (LPPM Institut Pendidikan Nusantara Global, 2026)
This study was motivated by how this humanistic approach can improve elementary school students' self-efficacy, which often hinders their academic potential. This study aims to analyze and observe teachers' implementation of the humanistic approach, specifically through communication, emotional support, and process-based feedback in improving students' self-efficacy. This study is a quantitative study with a survey approach involving 47 teachers and 40 students selected through purposive sampling. Data were collected using questionnaires and observation sheets, then analyzed and described descriptively. The findings indicate that teachers consistently implement humanistic approach practices such as friendly greetings and active communication that align with students' statements about feeling heard by their teachers. Furthermore, 95% of teachers provide verbal motivation when students experience difficulties and emphasize praise for efforts to increase students' confidence in their learning abilities. However, this study also identifies challenges in the form of environmental influences that can hinder this humanistic approach. The implications of this study suggest that schools integrate teacher personality competency development with comprehensive peer support interventions to create an inclusive learning environment.